2017
DOI: 10.1097/qad.0000000000001454
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B serological markers and plasma DNA concentrations

Abstract: Objectives:To examine hepatitis B (HBV) serological markers and plasma DNA concentrations in a large group of untreated HBV/HIV-coinfected individuals in two sub-Saharan settings.Design:Baseline analysis of a randomized controlled trial.Methods:DART was a large trial of treatment monitoring practices in HIV-infected adults with advanced disease starting antiretroviral therapy at centres in Kampala or Entebbe, Uganda (n = 2317) and Harare, Zimbabwe (n = 999). HBV serological markers [antibody to HBV core antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Furthermore, findings from Ejele et al, (2005) [ 23 ] and Olokoba et al, (2009) [ 24 ] in the country recorded far lower prevalence rates, of 1.1% and 2.4% respectively. This variation could be as a result of the study populations as studies have shown varying HBV prevalence among diverse groups and regions in the country and in fact across sub Saharan Africa [ 5 , 6 , 25 ]. The type of test kit used in screening may also be considered although this bias is inherent for all studies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, findings from Ejele et al, (2005) [ 23 ] and Olokoba et al, (2009) [ 24 ] in the country recorded far lower prevalence rates, of 1.1% and 2.4% respectively. This variation could be as a result of the study populations as studies have shown varying HBV prevalence among diverse groups and regions in the country and in fact across sub Saharan Africa [ 5 , 6 , 25 ]. The type of test kit used in screening may also be considered although this bias is inherent for all studies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This variation could be as a result of the study populations as studies have shown varying HBV prevalence among diverse groups and regions in the country and in fact across sub Saharan Africa [ 5 , 6 , 25 ]. The type of test kit used in screening may also be considered although this bias is inherent for all studies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have shown/reported various degrees of HBsAg loss and/or different seroconversion rates but found differences between coinfections and mono-infections, with higher rates in cases of coinfection. Cumulative HBsAg seroclearance rates of 5% to 22% have been reported (Jaroszewicz et al, 2012; Kosi et al, 2012; Maylin et al, 2012; Zoutendijk et al, 2012; Hamers et al, 2013; Matthews et al, 2013; Boyd et al, 2015; Huang and Nunez, 2015; Boyd et al, 2016; Lucifora and Protzer, 2016; Price et al, 2017). A recent meta-analysis focused exclusively on the suppression of HBV with TDF-containing ART (Price et al, 2013).…”
Section: Introductionmentioning
confidence: 99%